2010
DOI: 10.1007/s00401-010-0690-1
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric characterization of brain amyloid beta isoform signatures in familial and sporadic Alzheimer’s disease

Abstract: A proposed key event in the pathogenesis of Alzheimer’s disease (AD) is the formation of neurotoxic amyloid β (Aβ) oligomers and amyloid plaques in specific brain regions that are affected by the disease. The main plaque component is the 42 amino acid isoform of Aβ (Aβ1-42), which is thought to initiate plaque formation and AD pathogenesis. Numerous isoforms of Aβ, e.g., Aβ1-42, Aβ1-40 and the 3-pyroglutamate derivate of Aβ3-42 (pGluAβ3-42), have been detected in the brains of sporadic AD (SAD) and familial AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
323
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 286 publications
(353 citation statements)
references
References 40 publications
12
323
1
8
Order By: Relevance
“…FAD mutations can thus either inhibit or induce aggregation depending on the suitability of the replacing amino acid to accommodate an amyloidogenic or aggregated structure. Molecular dynamics simulations have suggested the depletion of the E22-K28 salt bridge to explain the enhanced aggregation of E22Q Ab , while the switch of a bend motif to a turn in the region Ab [22][23][24][25][26][27][28] could result in slower aggregation of the D23N Ab 1-42 mutant [25]. Overall fibril morphology is however not affected, as has been shown previously for a subset of FAD mutants [23].…”
Section: Discussionmentioning
confidence: 88%
“…FAD mutations can thus either inhibit or induce aggregation depending on the suitability of the replacing amino acid to accommodate an amyloidogenic or aggregated structure. Molecular dynamics simulations have suggested the depletion of the E22-K28 salt bridge to explain the enhanced aggregation of E22Q Ab , while the switch of a bend motif to a turn in the region Ab [22][23][24][25][26][27][28] could result in slower aggregation of the D23N Ab 1-42 mutant [25]. Overall fibril morphology is however not affected, as has been shown previously for a subset of FAD mutants [23].…”
Section: Discussionmentioning
confidence: 88%
“…We propose that in the presence of a Tyr10 O-glycosylation γ-secretase-dependent cleavage is modified, such that instead of cleavage at amino acid residues 40-42, the residues at 15-20 become the preferred cleavage sites (9,46). This hypothesis is based on the presence and structures of the Aβ1-X series of Tyr10 O-glycosylated peptides (Aβ1-15, 1-16, 1-17, 1-18, 1-19, and [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and the lack of glycosylated Aβ1-40/42 peptides in CSF. However, the appearance of Aβ peptides in CSF is the result of both complex production and clearance mechanisms (17).…”
Section: Discussionmentioning
confidence: 99%
“…In the amyloidogenic pathway β-and γ-secretases cleave APP into several Aβ isoforms (SI Appendix, Fig. S1) of which the 42 amino acid isoform (Aβ1-42) is one of the major constituents of amyloid plaques in the brains of AD patients (13). APP may also be cleaved in the middle of the Aβ1-42 sequence by α-secretase, precluding the formation of Aβ1-42 and thus considered to protect from amyloid deposition in the brain (9).…”
mentioning
confidence: 99%
“…Later immunohistochemical studies of human brain identified A␤ pE3 as a major component of A␤ plaques (12,13). More recently, immunoprecipitation in combination with mass spectrometry confirmed A␤ pE3-42 as a dominant A␤ isoform in the hippocampus and cortex of AD patients (14,15). Saido et al (12) suggested that removal of N-terminal amino acids 1 and 2 of A␤ might be carried out by a hypothetical amino or dipeptidyl peptidase(s), followed by a putative glutamate cyclization activity.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%